Pengaruh konsentrasi maltodekstrin dan putih telur terhadap karakteristik fisikokimia dan organoleptik sup krim instan labu kuning (curcubita moschata) - Ulya Sarofa; Riski Ayu Anggreini; Firsty Ainun Zalzabila Ansori (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Instant cream soup is a processed food product that is ready to be brewed or cooked using hot water so that it becomes a thick solution. This product is usually made from various flour ingredients, one of which is pumpkin flour and other additives. The purpose of this study was to determine the effect of the addition of maltodextrin and egg white on the quality of instant pumpkin cream soup using the foam drying method met drying. This study used a Completely Randomized Design two factors, with concentration of maltodextrin (5%; 10%; 15%) and egg white (10%; 15% 20%), with two repetitions. Data were analyzed using 5% ANOVA and 5% DMRT follow-up test. Pumpkin instant cream soup with the addition of 15% maltodextrin and 20% egg white concentration was the best treatment with yield value 26.08±0.060%, kamba density 0.61±0.007 g/mL, water content 6.31±0.028%, ash content 2.96±0.006%, protein content 12.19±0.028%, fat content 12 .06±0.003%, carbohydrate content 73.68±0.276%, color organoleptic test 3.75±1.146 (likes), taste 3.15±0.813 (likes), and aroma 3.25±0.761 (likes) and levels of β-carotene of 7.89±0.007 mg/100g.